Study on treatment of the-real silk print and dyeing wastewater with the anaerobic biotechnology under ambient temperature - SHEN Dong-sheng; LIU Xin-wen (浙江大学学报. 农业与生命科学版, 2005)
The combined anaerobic reactor was used to deal with low COD concentration wastewater from the real silk print and dyeing industry. When COD in influent was about 300 mg/L, influent color dilution factor was 400, the organic load was less than 1.0 kg COD/(m3·d) and 1.5 kg COD/(m3·d) and the hydraulic retention time was 10.8 hours and 5.5 hours, COD in the effluent was less than 100 mg/L and 150 mg/L, effluent color dilution factor was less than 50 and 80, respectively, which satisfied the national first and second rank discharge standard. It was demonstrated to be feasible by the technological and economical analysis.